Effectiveness of CSR Program in Social and Economic Development of the Community (Case Study at PT BSI Binjai Branch) - Dita Maharani; Raja Sakti Putra Harahap (SEAN Institute, 2025)
Corporate Social Responsibility (CSR) plays a vital role in supporting community welfare and enhancing corporate image, yet its implementation often faces various challenges. This study aims to specifically examine the obstacles, solutions, and effectiveness of the CSR program at PT. Bank Syariah Indonesia (BSI) Binjai Branch. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, then analyzed thematically. The findings reveal key challenges such as limited budgets, difficulty identifying community needs, weak stakeholder coordination, and low public participation. Solutions include prioritizing needs-based programs, conducting in-depth surveys, engaging stakeholders, and improving evaluation systems. These efforts have improved program effectiveness and encouraged greater community involvement. The results highlight the importance of participatory and transparent approaches in achieving sustainable CSR outcomes.